Madres e hijas - Priego, María Teresa ((La Rebelión de la Intimidad))
Incluye relatos de Angeles Mastretta, Sabina Berman, Carmen Boullosa, Elena Poniatowska, Sandra Lorenzano, Norma Lazo, María Teresa Priego, Lucía Melgar, Julia Cohen, Hortensia Moreno, Sara Poot Herrera y Julieta García González.